Never too late : a novel - Carr, Robyn ([Place of publication not identified] : Harlequin Books, 2015)
While recovering from a car accident, recently divorced Clare Wilson takes stock of her life and begins a transformation into a confident single woman who is happy to be on her own, which soon makes her the center of male attention.
Includes a reader's guide.
Keywords: Divorced women -- Fiction; Sisters -- Fiction; Traffic accidents -- Fiction; Love stories